Emerging Threats in Antifungal-Resistant Fungal Pathogens - Sanglard, Dominique (Frontiers in Medicine, 2016)
The use of antifungal drugs in the therapy of fungal diseases can lead to the development of antifungal resistance. Resistance has been described for virtually all antifungal agents in diverse pathogens including Candida and Aspergilli species. The majority of resistance mechanisms have also been elucidated at the molecular level in these pathogens. Drug resistance genes and genome mutations have been identified. Therapeutic choices are limited for the control of fungal diseases and it is tempting to combine several drugs to achieve better therapeutic efficacy. In the recent years, several novel resistance patterns have been observed including antifungal resistance originating from environmental sources in Aspergillus fumigatus and the emergence of simultaneous resistance to different antifungal classes (multidrug resistance, MDR) in different Candida species. This review will summarize these current trends.